Harmful effects of metal(loid) oxide nanoparticles - Soares, Eduardo V. (2021)
The incorporation of nanomaterials (NMs), including metal(loid) oxide (MOx) nanoparticles (NPs), in the most diversified consumer products, has grown enormously in recent decades. Consequently, the contact between humans and these materials increased, as well as their presence in the environment. This fact has raised concerns and uncertainties about the possible risks of NMs to human health and the adverse effects on the environment. These concerns underline the need and importance of assessing its nanosecurity. The present review focuses on the main mechanisms underlying the MOx NPs toxicity, illustrated with different biological models: release of toxic ions, cellular uptake of NPs, oxidative stress, shading effect on photosynthetic microorganisms, physical restrain and damage of cell wall. Additionally, the biological models used to evaluate the potential hazardous of nanomaterials are briefly presented, with particular emphasis on the yeast Saccharomyces cerevisiae, as an alternative model in nanotoxicology. An overview containing recent scientific advances on cellular responses (toxic symptoms exhibited by yeasts) resulting from the interaction with MOx NPs (inhibition of cell proliferation, cell wall damage, alteration of function and morphology of organelles, presence of oxidative stress bio-indicators, gene expression changes, genotoxicity and cell dead) is critically presented. The elucidation of the toxic modes of action of MOx NPs in yeast cells can be very useful in providing additional clues about the impact of NPs on the physiology and metabolism of the eukaryotic cell. Current and future trends of MOx NPs toxicity, regarding their possible impacts on the environment and human health, are discussed.